Renal cell carcinomas with tubulopapillary architecture and oncocytic cells: Molecular analysis of 39 difficult tumors to classify - Pivovarcikova, Kristyna; Grossmann, Petr; Hajkova, Veronika; Alaghehbandan, Reza; Pitra, Tomas; Perez Montiel, Delia; Sperga, Maris; Rogala, Joanna; Slisarenko, Maryna; Bartos Vesela, Adriena; Svajdler, Peter; Michalova, Kvetoslava; et al. (Annals of diagnostic pathology, 2021)
So-called oncocytic papillary renal cell carcinoma (OPRCC) is a poorly defined variant of papillary renal cell carcinoma. Since its first description, several studies were published with conflicting results, and thus precise definition is lacking. A cohort of 39 PRCCs composed of oncocytic cells were analyzed. Cases were divided into 3 groups based on copy number variation (CNV) pattern. The first group consisted of 23 cases with CNV equal to renal oncocytoma. The second group consisted of 7 cases with polysomy of chromosomes 7 and 17 and the last group of 9 cases included those with variable CNV. Epidemiologic, morphologic and immunohistochemical features varied among the groups. There were not any particular histomorphologic features correlating with any of the genetic subgroups. Further, a combination of morphologic, immunohistochemical, and molecular-genetic features did not allow to precisely predict biologic behavior. Owing to variable CNV pattern in OPRCC, strict adherence to morphology and immunohistochemical profile is recommended, particularly in limited samples (i.e., core biopsy). Applying CNV pattern as a part of a diagnostic algorithm can be potentially misleading. OPRCC is a highly variable group of tumors, which might be misdiagnosed as renal oncocytoma. Using the term OPRCC as a distinct diagnostic entity is, thanks to its high heterogeneity, questionable.
Keywords: DNA Copy Number Variations; dospělí; Kidney; diferenciální diagnóza; Female; Oxyphil Cells; Copy number variation pattern; Adult; překrývající se geny; ženské pohlaví; biopsie dutou jehlou; variabilita počtu kopií segmentů DNA; Immunohistochemistry; Adenoma, Oxyphilic; oxyfilní adenom; lidé; Biopsy, Large-Core Needle; staging nádorů; karcinom z renálních buněk; Overlapping; Aged, 80 and over; Unclassified; imunohistochemie; Diagnosis, Differential; Kidney Neoplasms; Carcinoma, Renal Cell; Humans; Middle Aged; Oncocytic renal cell carcinoma; Male; nádorové biomarkery; chromozomální aberace; Aged; Oncocytoma; nádory ledvin; Biomarkers, Tumor; hybridizace in situ fluorescenční; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Papillary; In Situ Hybridization, Fluorescence; oxyfilní buňky; Neoplasm Staging; Chromosome Aberrations; chybná diagnóza; Genes, Overlapping; Diagnostic Errors